Genetic and phylogenetic relationship of an American caprine rotavirus B strain with equine rotavirus B - Paul, Litty; Morgan, Jocelynn; Pulley, Gloria; Uprety, Tirth; Hause, Ben M.; Adam, Emma; Li, Feng; Carter, Craig N.; Marthaler, Douglas; Erol, Erdal (Frontiers in Virology, 2023)
Rotaviruses (RVs) are significant enteric pathogens of humans and animals. In March 2021, the University of Kentucky Veterinary Diagnostic Laboratory (UKVDL) received a fecal sample from a 1-week-old goat kid with diarrhea from a farm with 5 additional diarrheic kids. The fecal sample was tested negative for Bovine coronavirus, Bovine rotavirus Group A, E. coli K99+, Cryptosporidium parvum and Salmonella spp by multiplex real-time PCR assays. Interestingly, a novel Equine Rotavirus B (ERVB) in Kentucky was identified from neonatal foals also with watery diarrhea in the Spring of 2021. Once the ERVB-specific real-time PCR assay became available, the fecal sample from the goat kid was tested and found positive for RVB. Genome sequence of the caprine RVB from fecal sample was obtained using shotgun metagenomic sequencing by Illumina MiSeq. All of the eleven viral segments of caprine RVB were sequenced either completely or partially. Genetic and phylogenetic analysis of VP7, VP4, VP6, VP1–VP3, and NSP1- NSP5 genes indicated the caprine RVB strain had the genotype constellation of G3-P[3]-I3- R3-C3-M3-A4-N3-T3-E3-H3. In addition, the caprine RVB sequence showed the highest nucleotide identity and evolutionary relationship to the ERVB and previously sequenced caprine RVB strains. Given the similar geographical location of the equine and caprine strains from our study, these findings suggest a possible common source of infection.